Azilsartan Reduced TNF-α and IL-1β Levels, Increased IL-10 Levels and Upregulated VEGF, FGF, KGF, and TGF-α in an Oral Mucositis Model - de Araújo, Aurigena Antunes (PLoS One, 2015)
Oral mucositis (OM) is a common complication of treatments for head and neck cancer, particularly radiotherapy with or without chemotherapy. OM is characterised by oral erythema, ulceration, and pain. The aim of this study was to evaluate the effect of azilsartan (AZT), an angiotensin II receptor antagonist, on 5-fluorouracil (5-FU)-induced oral mucositis (OM) in Syrian hamsters. OM was induced by the intraperitoneal administration of 5-FU on experimental days 1 (60mg/Kg) and 2 (40mg/Kg). Animals were pretreated with oral AZT (1, 5, or 10 mg/kg) or vehicle 30 min before 5-FU injection and daily until day 10. Experimental treatment protocols were approved by the Animal Ethics Committee Use/CEUA (Number 28/2012) of the UFRN. Macroscopic analysis and cheek pouch samples were removed for histopathologic analysis. Myeloperoxidase (MPO), Malonyldialdehyde (MDA), interleukin-1 beta (IL-1β), interleukin-10 (IL-10), and tumour necrosis factor-alpha (TNF-α) were analysed by Enzyme Linked Immuno Sorbent Assay (ELISA). Vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), keratinocyte growth factor (KGF), and transforming growth factor (TGF)-α were measured by immunohistochemistry. Analysis of variance followed by Bonferroni’s test was used to calculate the means of intergroup differences (p ≤ 0.05). Treatment with 1 mg/kg AZT reduced levels MPO (p<0.01), MDA (p<0.5) and histological inflammatory cell infiltration, and increased the presence of granulation tissue. AZT treatment at 1 mg/kg reduced the TNF-α (p<0.05) and IL-1β (p<0.05) levels, increased the cheek pouch levels of IL-10 (p<0.01), and upregulated VEGF, FGF, KGF, and TGF-α. Administration of AZT at higher doses (5 and 10 mg/kg) did not significantly reverse the OM. AZT at a dose of 1 mg/kg prevented the mucosal damage and inflammation associated with 5-FU-induced OM, increasing granulation and tissue repair.